Growth Performance, Carcass Traits and Economics of Kadaknath birds Rearing under Intensive Condition in Hot and Humid Climate - Jena, P K; Panigrahi, B.; Panigrahi, B.; Panda, N.; Panda, N.; Mohapatra, L.M.; Mohapatra, L.M.; Mallik, B.K.; Mallik, B.K.; Bagh, J.; Bagh, J.; Pati, P.K.; et al. (Indian Journal of Animal Nutrition, 2020)
The experiment was conducted to study the growth performance, carcass traits and economics of Kadaknath chicken reared under intensive managemental condition in hot and humid climate of Odisha. A total of 104 day old straight run chicks of Kadaknath breed of chicken were taken for this experiment, divided into 4 replicates each comprising of 26 chicks and reared in deep litter system. The weekly body weight, feed conversion ratio (FCR), and mortality of birds were recorded upto 20th weeks of age and carcass traits were studied at the end of the experiment. No significant difference of body weight gain (p≥0.05) between male and female chicks was noticed upto 4th week while males showed higher (p≤0.05) body weights and gains from 5th to 20th week of age. The incidence of mortality recorded were 3.8% in the first week of age whereas no further mortality of birds noticed during rest of the experimental period. Males had higher (p≤ 0.01) slaughter weight, eviscerated weight and drumstick percentage, while females had higher (p≤0.01) breast and giblet percentage. Breast muscle showed higher crude protein, total ash compared to thigh muscle whereas lower ether extract and moisture was observed. From the above study it is concluded that Kadaknath breed can profitably be reared in intensive system of management in hot and humid climatic condition.